2014
DOI: 10.1515/sem-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

The taxicab-hailing encounter: The politics of gesture in the interaction order

Abstract: The forms of emblematic gesture and other communicative moves used in hailing taxicabs are shaped by the urban built environment and by the micro politics sparked by what Goffman called the "loose coupling" of the interaction and social orders. Cabdrivers evaluate street hails and choose whether or not to stop for prospective passengers; hailers seek to communicate their desirability as passengers within the limited mode of the street hail. The conditions and con straints that underlie the practice and recepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…We use the term "digitallyenabled service workers" to refer to workers who interact with consumers virtually before meeting in the physical space. Like taxi drivers (Anderson, 2014;Davis, 1959) and other traditional service workers (Leidner, 1999), digitally-enabled service workers need to evaluate interactional contexts, and thus manage emotional dis-plays during service encounters. Scholars have studied the power-relations between service workers and consumers (e.g., Leidner, 1999;Lopez, 2010) and the instrumentality and socio-economic forces of performing affective or emotional labor (e.g., Duffy, 2016;Gregg, 2010;Hearn, 2010;Hochschild, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…We use the term "digitallyenabled service workers" to refer to workers who interact with consumers virtually before meeting in the physical space. Like taxi drivers (Anderson, 2014;Davis, 1959) and other traditional service workers (Leidner, 1999), digitally-enabled service workers need to evaluate interactional contexts, and thus manage emotional dis-plays during service encounters. Scholars have studied the power-relations between service workers and consumers (e.g., Leidner, 1999;Lopez, 2010) and the instrumentality and socio-economic forces of performing affective or emotional labor (e.g., Duffy, 2016;Gregg, 2010;Hearn, 2010;Hochschild, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The topic of recognizing taxi street hailing has been studied by sociologists in order to explore how taxi drivers perceive and culturally interact with their environment, including passengers [ 39 ]. An interesting work is the work of Anderson, who studied gestures, in particular, as a communication channel between taxi drivers and passengers during hailing interactions [ 13 ]. Based on a survey that he distributed to a group of taxi drivers in San Francisco, CA, USA, the researcher wanted to explore how taxi drivers evaluate street hails in terms of clarity and propriety.…”
Section: Related Workmentioning
confidence: 99%
“…The current state of the art reveals that only two works have studied taxi street hailing from an interaction perspective. The first work is the study of Anderson [ 13 ], a sociologist who explored traditional taxi street hailing as a social interaction between drivers and hailers. Based on a survey that he distributed to a sample of taxi drivers, he found that the hailing gestures used by passengers largely vary in relation to the visual proximity of the hailer to the taxi and to the speed at which the taxi is passing [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of the existing “social-scientific-literature” focusing on the taxi relies mainly on texts from archives, on surveys or on interviews (see, e.g., Vidic 1976; Toiskallio 2000; Gambetta and Hamill 2005; Anderson 2014)—rarely on participant observation; also, most texts focus on various layers of the macro level —on taxi industries and on industrial relations (Biju 2005; Darbéra 2009; Darr 1999). Thus, the exploration of interaction rituals (Goffman 1983) routinely performed in the taxi remains almost untreated.…”
Section: Introductionmentioning
confidence: 99%